Moral Rationalization Contributes More Strongly to Escalation of Unethical Behavior Among Low Moral Identifiers Than Among High Moral Identifiers - Mulder, Laetitia B.; van Dijk, Eric (Frontiers in Psychology, 2020)
Occasional acts of immorality are commonplace. One way in which people deal with their own prior immoral acts, is to rationalize why their acts are morally acceptable. It has been argued that such post hoc moral rationalizations may contribute to continuation or escalation of immoral behavior. This paper experimentally tests this causal influence of post hoc moral argumentation on escalation of immoral behavior and also tests how this depends on people’s level of moral identity. In three experiments we asked participants to generate moral arguments for their past behaviors. The results show that engaging in moral rationalization causes subsequent continuation and escalation of previous immoral behavior, but more so for low moral identifiers than for high moral identifiers.